2022
DOI: 10.1097/pr9.0000000000000982
|View full text |Cite
|
Sign up to set email alerts
|

The Pain Coping Questionnaire short-form: preliminary reliability and validity

Abstract: Supplemental Digital Content is Available in the Text. A brief 16-item format of the Pain Coping Questionnaire was developed and found to have acceptable preliminary reliability and validity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Of these, 127 publications were excluded after full‐text review with a final 16 studies meeting eligibility for data extraction (Figure S1 ). These 16 studies reported on seven pain coping tools of which two have short forms and all have self‐report and observer‐reported outcome measure (parent proxy report) versions: the Bath Adolescent Pain Questionnaire (BAPQ) and Bath Adolescent Pain Questionnaire for Parents; 20 , 21 the Cerebral Palsy Quality of Life (CP QoL) teenager version, primary caregiver report, and self‐report; 22 the Child Self‐Efficacy Scale (CSES) self‐report and parent report; 23 the Fear of Pain Questionnaire (FOPQ) parent and self‐report and FOPQ short form self‐report; 24 , 25 the PPCI parent and self‐report; 26 the Pain Catastrophizing Scale for children (PCS‐C), parent and self‐report; 27 and the Pain Coping Questionnaire (PCQ) self‐report and parent report and the PCQ short form self‐report 28 , 29 (Table S3 ). The study populations included children and young adults with CP (11 studies), 10 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 intellectual disability (three studies), 40 , 41 , 42 spinal dysraphism (two studies), 32 , 43 and Down syndrome (two studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 127 publications were excluded after full‐text review with a final 16 studies meeting eligibility for data extraction (Figure S1 ). These 16 studies reported on seven pain coping tools of which two have short forms and all have self‐report and observer‐reported outcome measure (parent proxy report) versions: the Bath Adolescent Pain Questionnaire (BAPQ) and Bath Adolescent Pain Questionnaire for Parents; 20 , 21 the Cerebral Palsy Quality of Life (CP QoL) teenager version, primary caregiver report, and self‐report; 22 the Child Self‐Efficacy Scale (CSES) self‐report and parent report; 23 the Fear of Pain Questionnaire (FOPQ) parent and self‐report and FOPQ short form self‐report; 24 , 25 the PPCI parent and self‐report; 26 the Pain Catastrophizing Scale for children (PCS‐C), parent and self‐report; 27 and the Pain Coping Questionnaire (PCQ) self‐report and parent report and the PCQ short form self‐report 28 , 29 (Table S3 ). The study populations included children and young adults with CP (11 studies), 10 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 intellectual disability (three studies), 40 , 41 , 42 spinal dysraphism (two studies), 32 , 43 and Down syndrome (two studies).…”
Section: Resultsmentioning
confidence: 99%
“…In the original article by Reid et al, 28 a parent‐reported version was directly adapted from the child version and showed a moderate relationship with the self‐report version for both the Distraction and Emotional Focused Avoidance subscales; however, a weak relationship was reported for information seeking and cognitive distraction. In 2022, Kohut et al 29 published a short form of the PCQ, developed in a sample of 1225 children and adolescents. The short form demonstrates moderate evidence for construct validity.…”
Section: Resultsmentioning
confidence: 99%
“…Pain is a multidimensional and stressful experience including sensory, affective and cognitive components. Cognitive and behavioral processing with pain experience may be rigid and insufficient, enabling minor alleviation in stress and pain [ 22 ]. Pain coping scales, such as PCSped and PCSpar may function as qualitative clinical instruments as well as providing data for visualization of different coping resources the child and the parent has in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Validation in Finnish was accomplished by Marttinen et al [ 21 ]. Recently a short form of PCQ for children has been published [ 22 ] but ther are no existing questionnaire for assessing parents’ coping strategies when their child has pain, thus, there remained a need to create a corresponding scale for parents. Parents may enhance the child’s resilience with flexible coping abilities [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 1,187 cancer outpatients using the CSP, it was found that the patient’s level of education, income, and use of radiotherapy were the most significant predictors for achieving pain management goals [ 102 ]. A short form of the questionnaire is in development for use in pediatric patients with chronic pain [ 103 ]. Because this scale deals with coping mechanisms, it is vulnerable to cultural influences; a Spanish version of the CSP is available [ 104 ].…”
Section: Reviewmentioning
confidence: 99%